Deviation Analysis of Temperature Distribution in Copper Bar Heat Conduction Process Experiments Against Numerical Calculations - Ratu Fenny Muldiani; Kunlestiowati Hadiningrum; Defrianto Pratama (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
In the process of heat transfer by conduction, besides the quantities in the form of surface area, length or thickness of the rod, and the temperature difference between the ends of the rod and the value of the thermal conductivity, other factors also affect the rate of heat transfer to the rod, one of which is environmental factors. As long as heat flows from the high to the low temperature, the temperature decrease is not uniform at any time interval. This is a sign of the influence of the ambient temperature for each part of the material. Temperature observations were carried out experimentally in an open environment in the laboratory and then compared with the results of numerical calculations as the ideal condition for the heat conduction process. The Boltzmann transport equation for the induction process on metal rods is solved using finite differences with an explicit method to obtain the temperature distribution. The results showed differences in the temperature distribution pattern of copper rods with numerical calculations and experiments. This difference is caused by the amount of heat released into the environment. The higher the temperature at the observation point, the greater the heat released into the atmosphere.